2018
DOI: 10.1002/chem.201803042
|View full text |Cite
|
Sign up to set email alerts
|

NiII Complex Formation and Protonation States at the Active Site of a Nickel Superoxide Dismutase‐Derived Metallopeptide: Implications for the Mechanism of Superoxide Degradation

Abstract: A small, catalytically active metallopeptide (Nim SOD, m SOD=ACDLAC), which was derived from the nickel superoxide dismutase (NiSOD) active site was employed to study the mechanism of superoxide degradation, especially focusing on the protonation states of the Ni donor atoms, the proton source, and the role of the N-terminal proton(s). Therefore, the Ni -metallopeptide was studied at various pHs and temperatures using UV/Vis and NMR spectroscopy. These studies indicate a strong reduction of the pK of the Ni -l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…This conclusion is in contrast to that arising from an investigation carried out on metallopeptide-based models for which it has been proposed that protonation of one of the cysteines occurs during the catalytic mechanism . However, this is perfectly consistent with a more recent study performed on similar maquettes that show that the cysteine residues are not protonated …”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…This conclusion is in contrast to that arising from an investigation carried out on metallopeptide-based models for which it has been proposed that protonation of one of the cysteines occurs during the catalytic mechanism . However, this is perfectly consistent with a more recent study performed on similar maquettes that show that the cysteine residues are not protonated …”
Section: Discussionsupporting
confidence: 68%
“…26 However, this is perfectly consistent with a more recent study performed on similar maquettes that evidences that the cysteine residues are not protonated. 75 The SOD efficiency of NiL 3S (OH2) (IC50 ∼ 1 10 -6 M, pH 7.4) is lower than that of the NiSOD (IC50 = 4-8 10 -8 M per metallic site), 16 and the reaction is slower (kcat = 1.8 10 5 M -1 s -1 , pH 7.75) than that between O2 • -and NiSOD (kcat ∼ 1 10 9 M -1 s -1 , pH 6.0-8.0) 16 or peptide-based models (in the range 6 10 6 -6 10 8 M −1 s −1 , pH 8.0). However, the activity of the present Ni II SOD catalyst is expected to be enhanced at physiological pH, since the measured SOD activity at pH 7.75 contains a significant contribution of the inactive NiL 3S (OH) complex.…”
Section: Discussionmentioning
confidence: 99%
“…As stated above, NiSOD itself has been shown to possess at least one Ni-S(H + )-Cys moiety in its reduced form [15]. Although not without controversy [33], we have provided strong evidence based on sulfur K-edge X-ray absorption studies that like NiSOD itself, NiSOD metallopeptide based mimics possess a Ni-S(H + )-Cys moiety at physiological pH as well [18,22]. Studies have also suggested that the pK a of the Ni-S(H + )-Cys proton within these active-sites is~8.5, and can become reversibly deprotonated at high pH (>9.0) [22].…”
Section: General Considerationsmentioning
confidence: 97%
“…Taking advantage of the fact that all of the ligating residues to nickel are found within the first six residues from the protein N-terminus, we, and others, have prepared functional NiSOD metallopeptide based mimics utilizing the first 6-12 residues from the NiSOD N-terminal primary protein sequence. These metallopeptide based mimics reproduce the key structural and spectroscopic properties of the metalloenzyme [17,[26][27][28][29][30][31][32][33].Inorganics 2019, 7, x FOR PEER REVIEW 2 of 19 Chart 1. Representative structures of the active sites of cysteinate-ligated nickel containing metalloproteins.…”
mentioning
confidence: 97%
“…Such a chemical environment is unexpected considering the well-known reactivity between O 2 · – , H 2 O 2 , and even O 2 with metal-bound thiolates. Together with a poor understanding of the catalytic mechanism, especially due to the lack of characterized intermediate species, NiSOD has attracted the curiosity of the bioinorganic community. To face this challenge, it was not only crucial to develop catalytic NiSOD models active in water but also to trap intermediate species to provide key mechanistic insights. In this context, the ATCUN motif (ATCUN for amino terminal Cu II and Ni II binding motif) is an ideal choice to stabilize a square planar coordination for Ni II , which can be properly modulated with the introduction of a thiolate ligand through a cysteine residue to study the role and reactivity of the thiolate function.…”
Section: Introductionmentioning
confidence: 99%